Faktor faktor yang mempengaruhi permintaan deposito pada bank umum di provinsi Jambi - Ahlul Fikriyah, Gustina; Zulgani, Zulgani; Nurjanah, Rahma (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
Â The purpose of this study was to determine and analyze Gross Regional Domestic Product, interest rates and inflation on deposit demand for 2000-2017 period at Commercial Banks in Jambi Province. The method used in this research is quantitative descriptive analysis with multiple regression model analysis tools with the Ordinary Least Square (OLS) method. Data processing is performed using the Software Eviews 9.0 program. The results of this study the average development of deposits by 28.87 percent, Gross Regional Domestic Product by 6.20 percent, interest rates by -8.49 percent, inflation by 22.76 percent. Based on the results of the analysis conducted by the Gross Regional Domestic Product, interest rates and inflation have a positive and significant effect on demand for deposits with a coefficient of determination of 99.29 percent Keywords: Deposits, gross regional domestic product, interest rates, inflation